A phase 1 study of AL002 in healthy volunteers. (31st December 2021) - Ward, Michael; Long, Hua; Schwabe, Tina; Rhinn, Herve; Tassi, Ilaria; Salazar, Santiago Viveros; Rychkova, Anna; Tu, GuangHuan; Barner, Cheryl; Yeh, Felix L; Spencer, Madeline; Paul, Robert
Abstract: Background: Triggering receptor expressed on myeloid cells ‐2 (TREM2) is a prominent Alzheimer's disease (AD) risk gene that is expressed by microglia in the brain; reduced function of TREM2 is associated with a 3‐fold increase in AD risk. AL002 is a humanized monoclonal IgG1 antibody. The proposed mechanism of action is that it binds to TREM2 and activates the TREM2 signaling pathway to increase the ability of microglia to clear pathology and protect neurons with the goal of treating patients suffering from AD. INVOKE was a first‐in‐human Phase 1 study designed to investigate the safety, tolerability, pharmacokinetics and pharmacodynamics of intravenously administered AL002 in healthy volunteers (HV). Method: INVOKE was a randomized, placebo‐controlled, double‐blind investigation of AL002 in healthy volunteers (HV). The SAD portion of the study, which included a total of 64 HV receiving a single dose of 0.003 to 60 mg/kg AL002 or matching placebo is complete. Blood and CSF biomarkers were measured before dosing and at multiple timepoints after dosing. Result: In the SAD portion of the INVOKE study, AL002 was generally well tolerated in HV. AL002 decreased sTREM2 in cerebral spinal fluid (CSF), in a dose‐dependent manner, demonstrating proof of target engagement in the brain. Microglia biomarkers of TREM2 activation, such as CSF1R, SPP1 and IL1RN, were identified with in vitro and in vivo non‐clinical experiments. Consistent with these findings, treatment of HV with AL002 caused an increase in CSF levels of CSF1R, SPP1 and IL1RN in a dose‐dependent manner, suggesting proof of microglia activity through the TREM2 pathway. Conclusion: AL002 treatment resulted in TREM2 target engagement and proof of activity in the CSF of HVs. These results have supported progressing AL002 to an ongoing Phase 2 study (INVOKE‐2) to investigate its effects on cognitive decline and neurodegeneration in subjects with early AD.